Statistic tells: the regulatory pendulum of permit trajectories in China’s genetic governance (2021-2024) - Song, Lingqiao; Liu, Zhenyu; Meng, Fanlin (Frontiers in Genetics, 2025)
The regulation of human genetic resources in China exhibits distinct characteristics that emphasize national sovereignty. Under this framework, activities such as collection, preservation, export, and international collaboration of human genetic resources require an administrative license. This regulatory system began with the promulgation of the Interim Regulations on the Management of Human Genetic Resources in 1998, evolved with the Regulations on the Management of Human Genetic Resources in 2019 (as amended in 2024), and was further refined by the Implementation Rules of these regulations in 2023. This study examines official government statistics on administrative licensing for human genomic projects conducted between January 2021 and December 2024. Analysis indicates that following the adoption of the Implementation Rules, the overall number of licenses declined by 58.4% from 2023 to 2024 (n = 3,114), while the proportion of revoked licenses increased by 16.2%. Despite geopolitical influences, international cooperation licenses continue to be issued. Furthermore, the primary foreign entities remain multinational corporations headquartered in the United States, whereas domestic applicants are predominantly based in Beijing and Shanghai.